Trastorno de déficit de atención e hiperactividad en el proceso de aprendizaje en la educación inicial II - Rodríguez Gutiérrez, Anais Irlanda (2024)
Attention-deficit and hyperactivity disorder can occur in children in early education. This condition can affect their student performance, harming their learning process. Therefore, the present research aims to analyze the impact of attention-deficit and hyperactivity disorder in children. The learning process of level II initial education students. Therefore, in the “28 de Mayo” Educational Unit of the Urdaneta canton, Los Ríos province, this problem could be determined, which is why a documentary and exploratory type of research was used, which are essential in the collection of information with a mixed approach accompanied by a non-experimental design that allowed a correct preparation of the research work. The research aimed at ADHD in education resulted in that this disorder affects the academic development of students, harming their learning; however, it is important and crucial that teachers are prepared to meet the needs of those students who present ADHD. In conclusion, attention deficit hyperactivity disorder intervenes negatively in students' learning, therefore teachers must identify this problem in order to adapt their teaching, ensuring that children obtain correct academic performance without distractions due to said disorder.